2016
DOI: 10.1021/acssuschemeng.6b00280
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Epoxidation Reaction in the Absence of Surfactants—Integration of Reaction and Separation Steps in Microtubular Reactors

Abstract: This paper presents a paradigm shift with respect to the current direction of bi-phasic reactions in surfactant-free emulsions: herein, the contact area between both phases is simply sustained by the reactor design (i.e. diameter of the tubular reactor) compared to the current trend of using reversible/switchable emulsions where the addition of an external agent (e.g. bi-stable surfactant, magnetic particles, etc.) is required. In this way, temporally stable phase dispersions using micro-tubular reactors facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…However, at temperatures above 150°C decomposition of hydrogen peroxide dominates and the reaction yield is significantly reduced compared with the batch, lower‐temperature, process. A more recent study reported a lower temperature epoxidation of sunflower oil in an unstable two‐phase flow regime using surfactant‐less biphasic H 2 O 2 epoxidation catalysed by a W‐based system . The reaction system was not optimised for high per‐pass conversion, but the ease of phase separation after the reaction allowed simple re‐circulation to reach higher conversion in a loop‐reactor mode.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, at temperatures above 150°C decomposition of hydrogen peroxide dominates and the reaction yield is significantly reduced compared with the batch, lower‐temperature, process. A more recent study reported a lower temperature epoxidation of sunflower oil in an unstable two‐phase flow regime using surfactant‐less biphasic H 2 O 2 epoxidation catalysed by a W‐based system . The reaction system was not optimised for high per‐pass conversion, but the ease of phase separation after the reaction allowed simple re‐circulation to reach higher conversion in a loop‐reactor mode.…”
Section: Introductionmentioning
confidence: 95%
“…Epoxidation of cyclooctene using a sacrificial aldehyde reactant in the Mukaiyama epoxidation was performed in a segmented continuous flow microreactor, reporting 100% selectivity to the epoxide at a short residence time of 2 min . However, there are only two examples of epoxidation of triglycerides under flow conditions, the epoxidation of soybean oil and of sunflower oil …”
Section: Introductionmentioning
confidence: 99%
“…This result very common for the reaction in microreactor, because lower average flow velocity turn weakens the mass transfer [35] and therefore lower oxirane yields are obtained. It is worth to note that the residence time of 2.7 min is much smaller than that of the conventional batch which required several hours [1,5,6] and is in similar order to micro-flow reactor using homogeneous catalyst (6.7 min [17] and 10.6 min [12]). …”
Section: Effect Of Residence Timementioning
confidence: 99%
“…Moreover, a microreactor could operate under continuous flow operation and is easy to scale-up. Microreactor has been applied in many reactions and in both homogeneous [10][11][12][13] and heterogeneous [14][15][16] catalytic systems. Recently, He et al [17] investigated biphasic epoxidation reactions in a microreactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation